2013
DOI: 10.1001/jama.2013.2710
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Secretion and the Incidence of Type 2 Diabetes

Abstract: Importance Loss-of-function mutations in the melatonin receptor are associated with insulin resistance and type 2 diabetes. Additionally, in a cross-sectional analysis of persons without diabetes, lower nocturnal melatonin secretion was associated with increased insulin resistance.Objective To study the association between melatonin secretion and the risk of developing type 2 diabetes. Design, Setting, and Participants Case-control study nested within the Nurses' Health Study cohort. Among participants without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
206
3
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(232 citation statements)
references
References 53 publications
4
206
3
10
Order By: Relevance
“…Our data suggested that decreased melatonin signalling through deleterious MT2 receptor activity increases type 2 diabetes risk. These conclusions were in line with various studies done in rodents, beta cells and human cohorts, which showed that high melatonin levels, or the administration of melatonin or of melatonergic agonists, lead to decreased (and not augmented) risk of diabetes [9,13,14]. Indeed, for instance, a 12 year prospective study including 370 women who developed type 2 diabetes and 370 matched control participants showed that decreased levels of melatonin secretion during the night is independently associated with a higher risk of developing type 2 diabetes [13].…”
Section: Decreased Melatonin Signalling and Type 2 Diabetes Risksupporting
confidence: 89%
See 1 more Smart Citation
“…Our data suggested that decreased melatonin signalling through deleterious MT2 receptor activity increases type 2 diabetes risk. These conclusions were in line with various studies done in rodents, beta cells and human cohorts, which showed that high melatonin levels, or the administration of melatonin or of melatonergic agonists, lead to decreased (and not augmented) risk of diabetes [9,13,14]. Indeed, for instance, a 12 year prospective study including 370 women who developed type 2 diabetes and 370 matched control participants showed that decreased levels of melatonin secretion during the night is independently associated with a higher risk of developing type 2 diabetes [13].…”
Section: Decreased Melatonin Signalling and Type 2 Diabetes Risksupporting
confidence: 89%
“…These conclusions were in line with various studies done in rodents, beta cells and human cohorts, which showed that high melatonin levels, or the administration of melatonin or of melatonergic agonists, lead to decreased (and not augmented) risk of diabetes [9,13,14]. Indeed, for instance, a 12 year prospective study including 370 women who developed type 2 diabetes and 370 matched control participants showed that decreased levels of melatonin secretion during the night is independently associated with a higher risk of developing type 2 diabetes [13]. However, Tuomi et al showed in 45 individuals that 3 month exposure to a high dose of melatonin (4 mg per day) is associated with higher glucose values 90 min post glucose load [1].…”
Section: Decreased Melatonin Signalling and Type 2 Diabetes Risksupporting
confidence: 89%
“…Similar decrements in plasma melatonin levels during the night were also reported in diabetic patients with proliferative retinopathy relative to individuals without diabetes and diabetic individuals without retinopathy [149]. Though considerable evidence supports a positive correlation between lower night-time melatonin and increased risk of type 2 diabetes [50,139], not all data fully support this claim. Mantele and colleagues demonstrated that night-time melatonin levels were, in fact, elevated in obese individuals (compared with lean non-diabetic individuals) and unaffected in type 2 diabetic participants [150].…”
Section: Clinical Evidencementioning
confidence: 61%
“…Strikingly, a reduced level of night-time melatonin, as assessed by 6-sulfatoxymelatonin in morning urinary void, is positively associated with an increased risk of type 2 diabetes (Fig. 2) [50]. There is an emerging link between melatonin secretion, insulin secretion and abnormal glucose metabolism, and, thus, it is reasonable to hypothesise that altered/reduced melatonin levels may contribute to the development and severity of both metabolic and sleep disturbances in patients with type 2 diabetes.…”
Section: The Internal Timing System and Metabolic Dysfunctionmentioning
confidence: 99%
“…Numerous investigations have suggested that low melatonin levels may be associated with risks of breast cancer, 16 prostate cancer, 17 and type 2 diabetes. 18 Melatonin supplements may help sufferers of insomnia 19 and menopause. 20 The measurement of urinary melatonin 21 is also useful for monitoring levels of serum melatonin following oral administration.…”
Section: Introductionmentioning
confidence: 99%